KARAKTERISTIK LINDI HASIL FERMENTASI ANAEROBIK SAMPAH KOTA DALAM LISIMETER DAN POTENSI PEMANFAATANNYAMENJADI PUPUK CAIR - Damsir, Suprihatin, Muhammad Romli, Mohamad Yani, Arie Herlambang (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
This study aimed to characterize the content of the leachate from lisimeter and assess the potential for leachate as liquid fertilizer. Leachate samples were taken from 5 lisimeter containing municipal waste in various sizes; A=(powder), B=(0.1 cm – 0.9 cm), C=(1.0 cm–1.9 cm), D=(2.0 cm – 2.9 cm), and E=(Original). Observation was conducted to leachate quality during bioconversion in 150 days. Result shows that at all treatment of degradation rates in leachate gives decreasing value of BOD, COD,NH4-N, TKN, and Phospate (P) except Kalium (K+) which increased during the bioconversion process. The value of TKN, Phospate, and Kalium (K+) is within safe limit to be dishcarged to the environment in the form of liquid fertilizer. Pollutant characteristics in leachate after anaerobic fermentation treatment in the form of heavy metals Hg, Cr, Cd. Pb, Zn, and Cu analyzed from all treatment shows values within safe limits to be discharged to environment in the form of liquid fertilizer. However, levels of BOD, COD and NH4-N are not yet qualified for discharge and require further treatment.Keywords: leachate, municipal waste, anaerobic fermentation, lysimeter